Adaptation measures for the food and beverage industry to the impact of climate change on water availability. Issue 5 (26th January 2016) - Valta, K.; Moustakas, K.; Sotiropoulos, A.; Malamis, D.; Haralambous, K.J.
Abstract: Water is used as an ingredient, as an essential processing element, as a cooling agent and for the cleaning of equipment and installations in many food and beverage industries. Consequently, the sector is affected by the impact of climate change of reduced water availability. This paper presents current issues related to water demand in the food and beverage industry and addresses adaptation measures in response to reduced water availability. The food and drink industry is a large drinking quality water consumer. Owing to that, the sector has to adopt reduction and minimisation measures in line with the Best Available Techniques. In particular, some general measures can be adopted by all industries of the sector, while other measures are sector-specific measures including the meat and poultry processing sector, the fish processing sector, the fruit and vegetables division, dairies and the drink manufacturing industry. Through widespread adoption of water reducing and minimisation measures, the sector will move towards sustainable development achieving decoupling of economic growth from resource use as response to reduced water availability.